CONTROL APPROACHES OF THE CARBONATION COLUMN FOR SODA MANUFACTORING - CRISTEA, Vasile-Mircea (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The paper presents the design of decentralized control systems for the carbonation column of the ammonia-soda production process. The proposed control structures are tested based on an experimentally identified multiple-input-multiple-output dynamic model, capable of describing the behavior of the main carbonation column variables. Two new control structures are investigated. The first one proposes a new pairing of the manipulated to the controlled variables, based on the Relative Gain Array Matrix. The second one implements ratio control aimed to ensure the desired relationship between the inlet ammoniacal-brine and CO2 flows. Behavior of the designed control structures are tested in the presence of setpoint changes and action of typical disturbances. Results are compared to the traditional decentralized control system configuration in order to reveal both the incentives and the limitations of the proposed control structures.